2007
DOI: 10.1007/s11695-007-9235-7
|View full text |Cite
|
Sign up to set email alerts
|

Abdominoplasty after Weight Loss in Morbidly Obese Patients: A 4-Year Clinical Experience

Abstract: Abdominoplasty in the post-obese patient is an apparently simple procedure, which in fact causes a high rate of surgical complications. The complication rate is higher than that of cosmetic abdominoplasties. Nevertheless, the improvement in quality of life following such a procedure renders it a fundamental step in the rehabilitation of the formerly obese patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 30 publications
1
38
0
3
Order By: Relevance
“…Other authors raise the problem of higher morbidity rate and even perioperative deaths when these two procedures are combined, suggesting an interval of weight loss prior to the panniculectomy to make this procedure safer [29]. The risk of surgical complications following abdominoplasty in postbariatric patients is much higher than in patients scheduled for this procedure for cosmetic reasons [30].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors raise the problem of higher morbidity rate and even perioperative deaths when these two procedures are combined, suggesting an interval of weight loss prior to the panniculectomy to make this procedure safer [29]. The risk of surgical complications following abdominoplasty in postbariatric patients is much higher than in patients scheduled for this procedure for cosmetic reasons [30].…”
Section: Discussionmentioning
confidence: 99%
“…14 Fraccalvieri et al and Breiting et al reported that postbariatric patients have a significantly higher risk of developing complications after abdominoplasty, including wound infection and dehiscence, than non-postbariatric patients. 3,15 This is probably affected by the nutrition deficiency and micro-architecture changes of the skin that alter immunity and integrity of the skin through different mechanisms. 16 In the current study, our overall complication rate was high, approaching half of our patients (49% of patients).…”
Section: Discussionmentioning
confidence: 99%
“…3 We have defined postoperative complications as any minimal variation from the normal postoperative healing, although these complications did not suppose much discomfort to the patient. We have even included minor events such as small vertex skin necrosis with minimal wound dehiscence in the "anchor" incisions that would require daily care or small seroma that would need just drainage by punctuation in the outpatient clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Massive weight loss, as is increasingly stated in the medical literature [1][2][3][4][5], causes a multi-district pathology for the post-obese patient. Among the various diseases derived from the excessive cutaneous mantle, the tissue redundancy localised to limbs causes a relevant functional impairment for patients.…”
Section: Introductionmentioning
confidence: 99%